Effect of induced short-term heat stress on functions of liver and kidney of Swiss albinos mice (Mus musculus) (Albayan Scientific Journal, 2023)
Sixty sexually mature, 15 - 22 weeks old, males and femalesSwiss albinos weighing 21 to 43gm each were used to study the effect of heat exposure on their liver and kidney functions. The experimental design was 4 cells of 2 X 2 factorial arrangements for genders and heat treatments. The genders were: 30 male mice, and 30 female mice. The heat treatments were: The Control: 30 mice (15 males and 15 females) kept for four hours at room temperature (25 ± 2 0C), and The Heat Stress: 30 mice (15 males and 15 females) kept at 35 to 40 0C ambient temperature for four hours.Levels of the enzymes aspartate transaminase (AST), alanine transaminase (ALT), alkaline phosphatase (ALP), and total bilirubin (TOTAL BILI) in the serum were used to assess liver functions, while concentrations of serum Urea and Creatinine established the kidney functions.Mice exposed to 35 to 400C ambient temperature for four hours were normal during the first one to one and half hour of exposure, after that they became restless, dig in the saw dust, attempted to escape out of the cage, stopped feeding and drinking and their heart beat and respiration rate increased. This continued for another half an hour. After that they became dormant and lied in the corners of the cage until the end of the 4 hours heat exposure. In a separate experiment, mice that were not scarified but returned to normal room temperature after the exposure regained normal activity after 20 to 30 minutes.All differences in liver and kidney functions between Males and Females control groups were not statistically significant except for ALT which was higher in the Female group than in the Male group.Differences of values of AST, ALP and TOTAL BILI between the control treatments (Males, and Females) were not significant, but those of ALT were significant. All differences of AST, ALT, ALP and TOTAL BILI between the heat exposed treatments (Males and Females) were significant. Significant differences between the control and the heat exposed groups were also encountered. Differences in Urea and Creatinine concentrations between males and females control groups were not significant but were significant between the males and the female’s heat exposed groups. Those of the males or females heat exposed groups were significantly different from those of the control groups.